Advances in organometallic chemistry. - Perez, Pedro J., 1965- (Advances in organometallic chemistry, 2022)
Advances in Organometallic Chemistry, Volume 77, the latest release in this longstanding serial, is known for its comprehensive coverage of topics in organometallic synthesis, reactions, mechanisms, homogeneous catalysis, and more. It is ideal for a wide range of researchers involved in organometallic chemistry, with this updated release including chapters on Organometallic-like reactivity of group 10 metal-heteroatom sigma bonds, Organometallic interactions between metal nanoparticles and carbon-based molecules: a surface reactivity rationale, Group VI Allenylidene Complexes, and more.